Oral squamous cell carcinoma in rhesus macaque (macaca mulatta) (VETERINARIA, 2020)
This paper describes an oral squamous cell carcinoma with metastases into the lung in a 24-years-old female rhesus macaque (Macaca mulatta). At necropsy, 3.5 cm ulcerative, white grey, irregular mass with necrosis and loss of the muscle, and osteolysis of the mandibular bone was observed on the mentum. Histopathologically, the mass consisted of multiple highly cellular lobules of oval to polygonal cells in the abundant connective tissue stroma, and with high mitotic index. There were multifocal pearl-like foci of keratinized cells. Neoplastic cells were PAS negative. Immunohistochemically, positive labeling for high molecular weight cytokeratine (CKhmw) and negative labeling for CA antigen were obtained.
Keywords: neoplasia; histopathology; immunohistochemistry; monkey